The Relationship between Principles-Based Accounting Rules and Audit Fees - Drum, Dawna; Liu, Zenghui; Wan, Huishan (STIE Malangkucecwara, 2025)
This paper examines the relations between principles-based accounting standards and audit fees. Our empirical evidence suggests auditors charge a lower fee when firms’ standards are more principles based. Our result is consistent with the notion that principles-based accounting standards improve earnings quality and reduce auditor’s risk-related premium. Further analyses indicate this fee saving is more pronounced for firms with stronger corporate governance and firms in post-SOX era. The results add to the growing body of literature examining cost/benefit of principles-based accounting standards, as well as to the literature of the determinants of audit fees.